PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN PADA PERUMDA TIRTAULI PEMATANG SIANTAR - Regina Christian Sinaga; Kasmirudin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted at PERUMDA Tirtauli Pematang Siantar, Jl. Porsea no. 2 Pematang Siantar, North Sumatra. The problem in this study is that employee loyalty at PERUMDA Tirtauli Pematang Siantar is still relatively low, which can be seen from some employees who are less focused at work, or seem not sincere in mobilizing their energy in working in the company, and can also be seen from some employees who are negligent in carrying out their duties. The purpose of this study was to determine the effect of organizational culture on employee loyalty at PERUMDA Tirtauli Pematang Siantar.In this study, the method used is descriptive and quantitative analysis using the SPSS program. This population is the employees of PERUMDA Tirtauli Pematang Siantar, totaling 78 people. Methods of data collection using interviews and questionnaires. Hypothesis testing using simple linear analysis and multiple linear analysis.The research conducted shows that the results of the t test with organizational culture and work environment variables partially have a significant effect on employee loyalty. And the F test results show that simultaneously organizational culture and work environment have a significant effect on employee loyalty at PERUMDA Tirtauli Pematang Siantar with an R Square value of 0.703. This shows that organizational culture and work environment have an effect of 70.3% on employee loyalty in the Good Enough category, while the remaining 29.7% is influenced by other variables not examined in this study.Keywords: organizational culture, work environment, loyalty